KAJIAN PENERAPAN MODEL GUIDED DISCOVERY LEARNING DISERTAI CONCEPT MAP TERHADAP PEMAHAMAN KONSEP SISWA SMA KELAS XI PADA MATERI SISTEM IMUN - Arifiana Nur Kholifah; Yudi Rinanto; Murni Ramli (Universitas Sebelas Maret, 2015)
Research aims to analyze the impact of Guided Discovery Learning model combined with Concept Map toward concept understanding on immune system of students grade XI. The research was a quasi-experimental research with post-test only with non-equivalent groups. The population was all classes of grade XI IPA of SMA N 6 Surakarta. The sampling technique was cluster sampling and data was collected by test and non test method. A multiple choice test and essays was developed to measure students concept understanding on immune system. Meanwhile, the non test methods consisting of documentation, observation, and questionnaire were developed to asses the learning process, psychomotoric, and affective domain. Hypothesis test were analysed by t-test using SPSS version 16. The result are Guided Discovery Learning models with Concept Map is more effective to improve concept understanding on immune system of student, and it also found that students have most misconceptions in mechanism of immune system, antigen and antibody, and also affect of immune system. Keywords: Guided Discovery Learning, Concept Map, concept understanding